Empyema Thoracis In Children-A Study From Tertiary Care Hospital - AUNDHAKAR, C.D.; VARGHESE, TANYA (International Journal of Psychosocial Rehabilitation, 2025)
Aims and objectives –to know clinical profile,antibiotic sensitivity of organisms and effectiveness of medical therapy and pleural drainage in managing empyema in childrenMethods- Prospective cohort studySetting-Krishna hospital,KaradPatients-30 children between 6 months-13 years admitted with empyema from March 2018-February 2019 were studied and data was analysed using appropriate statistical methods.Results– During the study period, 30 children (20 males) were identified with empyema with a median (range) age at presentation of 4 years (6 months-13 years). Fever, dyspnea and cough were the most common (90%) manifestations at admission. Median (range) duration of fever was 10 days (5 days - 1month). The pleural fluid aspirated was thick pus in 80%; pleural fluid sugars were less than 40 mg/dL in 75% samples. Pleural liquid culture developed Staphylococcus aureus in 7 youngsters, and Streptococcus pneumoniae in 1 kid. Blood culture was certain just for one patient. 25 patients(84%) indicated clinical improvement after the beginning of anti-infection agents. In many patients (56%) fever died down inside 5 days after confirmation with a middle length of 4 days. The middle span of respiratory pain during medical clinic remain was 6 days. 5 patients got the second line anti-infection agents following five days of confirmation. 20 (68%) patients got anti-infection agents (oral in addition to parenteral) for about a month and 12% for a period more noteworthy than about a month and a half. The middle length of chest tube inclusion was 8 days, however 4 patients had drawn out chest tube seepage (2 indicated deferred response,2 created bronchopleural fistula). Three patients required more than one chest tube taking into account loculated effusion. The minimum duration of hospital stay to complete the course of injectable antibiotics was 14 days.Conclusion- Fitting anti-infection agents and brief chest tube drainage is a powerful strategy for treatment of youth empyema, particularly in asset poor settings.